2012
DOI: 10.1111/j.1601-5215.2011.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired working memory and normal sustained attention in borderline personality disorder

Abstract: P. Impaired working memory and normal sustained attention in borderline personality disorder.Objective: Although reports in the literature describe deficits in working memory in borderline personality disorder (BPD), the evidence is limited and inconsistent. The aim of this study was to evaluate further this cognitive dimension and its clinical correlates in BPD. Method: We compared the performance of 15 BPD patients to 1:1 matched healthy controls on verbal working memory as determined by the sequential lette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(69 reference statements)
3
3
0
Order By: Relevance
“…The N2 latency WM load-independence might occur because the speed of processing for a 0-back task is not different from that of a 2-back task. For P3 amplitude, consistent with other studies (Posner et al, 2002; Stevens et al, 2004; Lazzaretti et al, 2012), we found no correlation between P3 amplitude and affect intensity or impulsiveness suggested that the diminished P3 amplitude was not modulated by affect intensity and impulsiveness. Previous studies found that the information processing stages are not parallel, and those impairments in one stage may affect other stages (Di Russo et al, 2010; Portella et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The N2 latency WM load-independence might occur because the speed of processing for a 0-back task is not different from that of a 2-back task. For P3 amplitude, consistent with other studies (Posner et al, 2002; Stevens et al, 2004; Lazzaretti et al, 2012), we found no correlation between P3 amplitude and affect intensity or impulsiveness suggested that the diminished P3 amplitude was not modulated by affect intensity and impulsiveness. Previous studies found that the information processing stages are not parallel, and those impairments in one stage may affect other stages (Di Russo et al, 2010; Portella et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…But only a few studies have considered WM in BPD, and the results have been inconsistent. For example, whereas some studies found a WM deficit in BPD populations (O’Leary, 2000; Stevens et al, 2004; Lazzaretti et al, 2012), others did not (Sprock et al, 2000; Judd, 2005; Gvirts et al, 2012). When normal populations engage in a WM task, the parietal cortex and dorsolateral prefrontal cortex are activated (Curtis, 2006; Fang et al, 2016; Ng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this lack of inhibitory control leads to engagement in more risky and impulsive behaviour, although this relation remains untested by the current study. This finding that adolescents with a predominantly externalizing BPD presentation were rated as having poorer working memory than adolescents with a predominantly internalizing presentation is consistent with prior work in adults demonstrating that highly impulsive individuals with BPD exhibit the most difficulty with working memory 56 and suggests that perhaps working memory impairments may differentially relate to internalizing and externalizing BPD presentations. Although prior research examining the relation between working memory and BPD in adults has been unclear, with some studies reporting definitive working memory deficits in individuals with BPD, [56][57][58] and others finding no such deficits, 34,59 our finding may bridge this gap, indicating that the heterogeneity of BPD symptomatology may be contributing to this discrepancy.…”
Section: Discussionsupporting
confidence: 87%
“…In fact the task in the last two blocks requires a higher working memory load, since the subject must keep in mind both categories to give the CR. Deficits in neuropsychological performance in BPD when working memory demands are high has been demonstrated elsewhere in our previous work (Sala et al, 2009; Lazzaretti et al, 2012). This finding supports the relationship between working memory load and impulsivity, that has been already demonstrated in literature (Hinson et al, 2003).…”
Section: Discussionsupporting
confidence: 76%